Dynamic Secrets in Communication Security - Xiao, Sheng; Gong, Weibo; Towsley, Don.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Dynamic secrets are constantly generated and updated from messages exchanged between two communication users. When dynamic secrets are used as a complement to existing secure communication systems, a stolen key or password can be quickly and automatically reverted to its secret status without disrupting communication. "Dynamic Secrets in Communication Security" presents unique security properties and application studies for this technology. Password theft and key theft no longer pose serious security threats when parties frequently use dynamic secrets. This book also illustrates that a dynamic secret based security scheme guarantees impersonation attacks are detected even if an adversary steals a user$1 (Bs password or their key is lost. Practitioners and researchers working in network security or wireless communications will find this book a must-have reference. "Dynamic Secrets in Communication Security" is also a valuable secondary text for advanced-level students in computer science and electrical engineering.s
Introduction -- Communication Security and Key Safety -- Dynamic Secrets -- Dynamic Wireless Security -- Dynamic Key Management in a Smart Grid -- Secrecy in Communications -- Reliability Analysis for Communication Security -- Future Applications.
Keywords: Computer science; Computer Communication Networks; Data protection; Data structures (Computer science).; Data encryption (Computer science).; Telecommunication; Computer Science; Systems and Data Security; Computer Communication Networks; Data Encryption; Data Structures, Cryptology and Information Theory; Communications Engineering, Networks